2021
DOI: 10.1016/j.scitotenv.2020.143084
|View full text |Cite|
|
Sign up to set email alerts
|

Specific enrichment of hydrocarbonclastic bacteria from diesel-amended soil on biochar particles

Abstract: HIGHLIGHTS• Biochar was evaluated for the biostimulation of hydrocarbon contaminated soils.• Amplicon sequence variants (ASVs) reveal specific soil microbial responses to oil.• Oil amplifies 13 ASVs -putative hydrocarbon degraders -to high relative abundance.• Standard biochars reduce soil diversity loss and are enriched in oil-selected ASVs.• Biochar enriched with endogenous microbes is a promising approach to bioremediation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 78 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…Fang et al 10.3389/fmicb.2024.1343366 Frontiers in Microbiology 12 frontiersin.org phyla were relatively abundant: Acidobacteriota, which may be related to soil organic matter content (Shelyakin et al, 2022); Gemmatimonadota, which participates in the detoxification and degradation of organic pollutants and has a high tolerance to organic pollutants (Zhang et al, 2022); and Actinobacteriota, which has been reported as one of the most common bacteria in oil-contaminated soils (Egorova et al, 2023). At the genus level, Cavicella with the high relative abundance in this study, is a recently discovered genus that is more likely to be enriched in crude oil-contaminated soils or diesel-contaminated soils and may contain novel petroleum hydrocarbon-degrading bacteria (Xue et al, 2020;Assil et al, 2021). C1_B045 is still poorly documented although it has been detected in some oil pollution studies (Teske et al, 2022).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Fang et al 10.3389/fmicb.2024.1343366 Frontiers in Microbiology 12 frontiersin.org phyla were relatively abundant: Acidobacteriota, which may be related to soil organic matter content (Shelyakin et al, 2022); Gemmatimonadota, which participates in the detoxification and degradation of organic pollutants and has a high tolerance to organic pollutants (Zhang et al, 2022); and Actinobacteriota, which has been reported as one of the most common bacteria in oil-contaminated soils (Egorova et al, 2023). At the genus level, Cavicella with the high relative abundance in this study, is a recently discovered genus that is more likely to be enriched in crude oil-contaminated soils or diesel-contaminated soils and may contain novel petroleum hydrocarbon-degrading bacteria (Xue et al, 2020;Assil et al, 2021). C1_B045 is still poorly documented although it has been detected in some oil pollution studies (Teske et al, 2022).…”
Section: Discussionmentioning
confidence: 77%
“…At the genus level, Cavicella with the high relative abundance in this study, is a recently discovered genus that is more likely to be enriched in crude oil-contaminated soils or diesel-contaminated soils and may contain novel petroleum hydrocarbon-degrading bacteria ( Xue et al, 2020 ; Assil et al, 2021 ). C1_B045 is still poorly documented although it has been detected in some oil pollution studies ( Teske et al, 2022 ).…”
Section: Discussionmentioning
confidence: 94%
“…At day 7, the relative abundance of these genera slightly decreases and they are outperformed by Aquabacterium , which is the most abundant genus. Aquabacterium has been identified as an oil degrader [ 57 ], and was strongly stimulated by diesel in a previous incubation study [ 58 ]. Another enriched genus at day 7, Novosphingobium , was also observed in high abundance in a diesel-related microbiology study [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Phenylobacterium were found to be enriched in soil after plastic mulching treatments (Luo et al, 2022) and these bacteria are capable of degrading polycyclic aromatic hydrocarbons (Yang et al, 2014). Only for Cavicella a link to MP materials in soils has not be described, but the genus is known as hydrocarbonoclastic (Assil et al, 2021) and has at least the potential to utilize the carbon of the MP materials.…”
Section: Especiallymentioning
confidence: 99%